Differentiated perceived match load and its variability according to playing position in professional soccer players during an entire season (Kinesiology, 2020)
The aims were to assess differentiated perceived match exertion and its variability according to playing position for professional soccer players. Nineteen Spanish players declared their respiratory and muscular perceived exertions after official matches during an entire season. Players were classified according to their playing position. In order to assess differentiated perceived match exertion, soccer players were asked to assess their perceived level of exertion following each official match. Considerable differences (p